Antibacterial effects of bioactive restorative dental materials on Streptococcus mutans: An in vitro study using the direct contact test - Sirirat Boondireke; Onsasi Kitrueangphatchara; Charnsak Sukajintanakarn; Sirichan Chiaraputt (The Saudi Dental Journal, 2025)
This in vitro study aimed to evaluate the antibacterial activity of various restorative dental materials against Streptococcus mutans, a major cariogenic pathogen. The materials tested included a resin composite (Estelite Sigma Quick), conventional glass ionomer cement (Fuji IX), resin-modified glass ionomer cement (Fuji II LC), a bioactive resin-based material (Activa BioACTIVE Restorative), and a calcium silicate-based material (Biodentine). Antibacterial activity was assessed using the direct contact test (DCT). Each material was tested against S. mutans at 3, 6, 16, and 24-h intervals. Colony-forming units (CFU) were quantified following serial dilution and culture on BHI agar. Statistical comparisons were conducted using the Kruskal-Wallis test. All materials except Estelite demonstrated significant antibacterial effects. Biodentine exhibited the greatest inhibition (P ≤ 0.001), followed by Fuji IX (P ≤ 0.001), and Fuji II LC (P ≤ 0.01). Activa BioACTIVE showed significant bacterial reduction at 16 and 24 h (P ≤ 0.05). Estelite showed no significant antibacterial effect (P > 0.05). Biodentine displayed sustained and pronounced antibacterial effects, suggesting its suitability for patients at high risk of caries. Fuji IX and Fuji II LC also exhibited antibacterial properties, though to a lesser extent. The findings support the use of bioactive restorative materials in managing bacterial presence and enhancing restoration longevity. The superior antibacterial performance of Biodentine highlights its potential role in preventing secondary caries, particularly in high-risk populations. Clinicians are encouraged to consider bioactive materials as part of comprehensive caries management strategies.
Keywords: Oral microbiology and periodontitis research; Dental materials and restorations; Endodontics and Root Canal Treatments